Electric Cars For Enlightened Stars. - Voelcker, J. (IEEE spectrum)
This paper presents the Tesla roadster, created by a start-up, Tesla Motors. It is powered by lithium-ion batteries. It is a zero-carbon vehicle a new fashion accessory for actors like George Clooney